Efektivitas Pembelajaran Matematika Melalui Penerapan Pendekatan Kontekstual Pada Siswa Kelas VIII SMP Negeri 3 Sulabesi Tengah - Yani Awal (Peneliti.net, 2022)
This type of research is a pre-experimental study involving one class as an experimental class which aims to determine the Effectiveness of the Application of the Contextual Approach in Learning Mathematics in Class VIII Students of SMP Negeri 3 Central Sulabesi. This study refers to the criteria of learning effectiveness, namely: learning outcomes which include individual and classical learning mastery, as well as gain or increase in learning outcomes, student activities in participating in learning, student responses to the learning process and, learning implementation. The research design used was The One Group Pretest Peosttest design. The experimental sample was class VIII students at SMP Negeri 3 Central Sulawesi with a total of 30 students. The data collection technique used was a learning achievement test, student activity observation sheets and student response questionnaires, as well as learning implementation sheets. The results showed that: the pretest average score was 46.4 and the posttest average score was 80.43 with a standard deviation of 15.78 for each pretest and 6.45 for posttest. From these results it was found that 27 out of 30 students or 90% had achieved individual mastery and this meant that classical mastery had been achieved. In addition, there was an increase in student learning outcomes after applying learning through the Contextual Approach where the average value of students' normalized gain was 0.63 in the medium category with an interval range of 0.30 ≤ g < 0.7. The average percentage of student activity is 81.78% and is in the range of 76% - 85%, so student activity reaches the active criteria. Students gave positive responses where the average percentage was 97.5%. The average implementation of learning or the teacher's ability to manage learning is 3.81 and is generally in the very good category because it is in the range of 3.5 < KG ≤ 4.0. From the results of the study it can be concluded that, through the application of the Contextual Approach it is effectively applied in learning mathematics in class VIII students of SMP Negeri 3 Central Sulabesi.